The "out the box"legal research: in search of new trends - Napoleone, Luciana Maria; Camargo, Emília da Conceição; dos Santos, Emanoel Vitorino (Qualitative and Quantitative Methods in Libraries; Vol 5 No 4 (2016): December 2016 Issue, 2017)
"Out-of-the-box" research strategies are inquiries where the interaction between information professionals and clients demand sharing data as well as applying interdisciplinarity, and whose solutions lie beyond the information available on structured databases. As methods were used literature review and an exploratory study made by data sampling with many specialized professionals, mainly from São Paulo city, the largest services market in Latin America. The identified strategies and resources are presented and analyzed, according to the points of view found in the literature, and to the authors' experience. The "out of the box" research strategies tend to become a new competence required for the information professionals in legal area.